ETIKA BISNIS PEDAGANG MUSLIM DI PASAR SENTRAL GORONTALO PERSPEKTIF HUKUM BISNIS ISLAM - Rizal Darwis (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2017)
Ethics are the standard value which serves as a guideline for social activities. Ethical behavior in business is very important to achieve long-term success in a business. This study examines how business practices and ethics are conducted by Muslim traders in Gorontalo Central Market under Islamic business law perspective. This research is field research with qualitative method. The approach used was Islamic business law approach and sociology-economic approach. Data was collected through documentation, observation, interviews, and questionnaires. Sampling technique was based on a random sampling of 175 traders with 883 populations. The data obtained was processed and analyzed by qualitative descriptive. The results indicated that Muslim traders in Central Market of Gorontalo are still prone to cheating. Ethical issues in business according to Islamic law have not become an appropriate guide